An Arabidopsis mutation in translation elongation factor 2 causes superinduction of CBF/DREB1 transcription factor genes but blocks the induction of their downstream targets under low temperatures - Guo, Yan (The National Academy of Sciences, 2002)
Low temperature regulates gene expression in bacteria, yeast, and animals as well as in plants. However, the signal transduction cascades mediating the low temperature responses are not well understood in any organism. To identify components in low temperature signaling genetically, we isolated Arabidopsis thaliana mutants in which cold-responsive genes are no longer induced by low temperatures. One of these mutations, los1–1, specifically blocks low temperature-induced transcription of cold-responsive genes. Surprisingly, cold-induced expression of the early response transcriptional activators, C-repeat/dehydration responsive element binding factors (CBF/DREB1s), is enhanced by the los1–1 mutation. The los1–1 mutation also reduces the capacity of plants to develop freezing tolerance but does not impair the vernalization response. Genetic analysis indicated that los1–1 is a recessive mutation in a single nuclear gene. The LOS1 gene encodes a translation elongation factor 2-like protein. Protein labeling studies show that new protein synthesis is blocked in los1–1 mutant plants specifically in the cold. These results reveal a critical role of new protein synthesis in the proper transduction of low temperature signals. Our results also suggest that cold-induced transcription of CBF/DREB1s is feedback inhibited by their gene products or by products of their downstream target genes.